Innovation of the WTO on procedures for foreign trade in goods - GALKO Світлана; TERESHCHENKO Сергій (Ius Modernum, 2019)
Background. The existence and compliance of international rules for trade in goods suggested by the World Trade Organization (WTO) ensure the confidence and stability for international trade. Barriers for trading countries are pressing issues of the last decades at the global level, and the focus on tariff issues is no longer put today. Analysis of recent researches and publications. Both politicians and scientists from all over the world have always been engaged in and continue to study the relevant and discussed in the framework of the WTO issues of international trade. At the same time, given the importance and breadth of this problem, the issues of the modern development of international trade, the main directions of such development, require further comprehensive study and analysis. The aim of the article is the analysis of the innovative aspects of the Trade Facilitation Agreement (TFA), as a new vector for the development of international trade in goods suggested by the WTO. Materials and methods. The study was conducted using general scientific methods: a systematic approach, theoretical generalization and comparison, analysis and synthesis. The information base was the current regulatory legal acts of Ukraine, incl. Trade Facilitation Agreement, WTO working materials, scientific articles and dictionaries. Results. The WTO Trade Facilitation Agreement (entered into force on 22 February 2017) has become one of the consequences of clarification and improvement of existing articles V, VIII and X of the GATT 1947 and the result of lengthy multilateral negotiations on the rules in the field of trade facilitation. The Agreement on Trade Facilitation within the WTO sets a new vector for the development of international trade in the direction of unification and simplification of the procedural issues of administering world trade in goods, in particular, the procedures available to the entry / exit of goods, the cooperation of border control authorities, the movement of goods under customs control, release and customs clearance of goods, transparency, appeal of decisions, payments and fines, customs formalities and documentation. Conclusion. A chronological analysis of multilateral trade negotiations within the WTO, an assessment of the content of the Agreement on Trade Facilitation, which is an integral part of the WTO legal framework, as well as the structure of this agreement, outlined in the article, allow us to state that the issues of regulation at the international level of tariff control measures have been exhausted. As we can see, the emphasis in the international plane has shifted from tariff regulation methods to procedural measures, therefore the procedural issues, the control of compliance with formalities when moving goods through customs borders, should be given priority attention at the national levels. At the same time, the understanding and research of the unified provisions of the Agreement on Trade Facilitation should be continued in order to correlate them with other international agreements and conventions, which define the key provisions on behalf of procedures carried out in the course of international trade in goods.